Critical Pedagogy in an EFL Context: Towards Solving the Definition Precision Problem - Leila Akbarpour (Vision: Journal for Language and Foreign Language Learning, 2022)
Some critics mention the definition variety problem, or a lack of definitional precision, as a major problem with Critical Pedagogy (CP). One who has just been familiar with CP may not have enough information regarding its roots and its multidisciplinary nature. S/he may not know about the historical development of CP and thus may not even be acquainted with the possibility of the existence of different definitions and versions for CP. Therefore, a newly-arrived researcher may get confused encountering the different definitions of CP. On the other hand, the literature on CP does not seem to be directed at the new researchers. By having five phases, the present mixed-methods study offered a simple definition of CP encompassing all the common grounds in the literature using an extensive literature review, the Grounded Theory approach, and Factor Analysis. Ten Iranian EFL professionals in CP, besides 306 Iranian EFL teachers, participated in the present work. The results of the present work may be helpful in developing CP-based curricula and courses which look into the real needs of the learners and teachers in order to have a more fruitful educational system.